Seleksi Progeni F1 Sebagai Klon Unggul Penghasil Lateks dan Lateks Kayu - Amorrito Surbakti; Rosmayati Rosmayati; Luthfi A. M. Siregar (Jurnal Agroekoteknologi, 2015)
The objective of this research was to get the best progeny based on potential of latex yield characteristic, timber yield characteristic and latex-timber yield resulted from 2008 hand pollination. The research was conducted in ± 54 m above sea level at Balai Penelitian Sungei Putih Pusat Penelitian Karet Galang Deli Serdang Sumatera Utara Medan from February 2014 - July 2014. The research was done by measuring coefisien varians, correlation, regression, path analysis, 10 % and 1 % selection intensity, and two line pattern.The research showed based on selection latex yield are 172/08 (intensity 10% and 1%), based on selection timber yield with intensity 10 % and 1 % are 172/08 and 173/08. Progeny 172/08 potential as latex and timber yielding for 2008 hand pollination.Keywords :Hevea brasiliensis, progeny,path analysis, selection